Embedded systems design with special arithmetic and number systems - Molahosseini, Amir Sabbagh; Seabra de Sousa, Leonel; Chang, Chip-Hong (Springer, 2017)
This book introduces readers to alternative approaches to designing efficient embedded systems using unconventional number systems. The authors describe various systems that can be used for designing efficient embedded and application-specific processors, such as Residue Number System, Logarithmic Number System, Redundant Binary Number System Double-Base Number System, Decimal Floating Point Number System and Continuous Valued Number System. Readers will learn the strategies and trade-offs of using unconventional number systems in application-specific processors and be able to apply and design appropriate arithmetic operations from these number systems to boost the performance of digital systems." Serves as a single-source reference to designing embedded systems with unconventional number systems " Covers theory as well as implementation on application-specific processors " Explains mathematical concepts in a manner accessible to readers with diverse backgrounds.